Strategic Communication And Corporate Branding: A Study Of Unilever Indonesia - Zinaida, Rahma Santhi; Sulistyanto, Apri Dwi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The existence of a company is determined by the company's identity. This aspect is very important because it is a very clear differentiator to other companies or competitors in the same industry. Brand identity, corporate culture and brand personality are some indicators that can show the strength of a corporate identity. This research will focus on PT. Unilever Indonesia as the object. The main issue to be investigated in this research is how Unilever builds its corporate identity through its corporate communication strategies. The method used in this research is literature study and Unilever corporate video observation. From the findings of the author, PT. Unilever has consistently strengthened its organizational identity from time to time. This consistency can be seen from the many innovations made, the corporate communication channels used, as well as the adaptation of the world and digital technology developments that occur. The journey of 88 years to finally become Market Leaders in Indonesia today, is the result of strengthening corporate identity in various forms such as strategy choice, corporate expression, brand image, to reputation. Public Expose 2022 further emphasizes the corporate identity of PT. Unilever Indonesia as a market leader with a very strong image. This research will contribute to the enrichment of information about the corporate identity of PT. Unilever is getting stronger as a market leaders company in Indonesia